2018
DOI: 10.1016/j.celrep.2018.02.043
|View full text |Cite
|
Sign up to set email alerts
|

CEP128 Localizes to the Subdistal Appendages of the Mother Centriole and Regulates TGF-β/BMP Signaling at the Primary Cilium

Abstract: The centrosome is the main microtubule-organizing center in animal cells and comprises a mother and daughter centriole surrounded by pericentriolar material. During formation of primary cilia, the mother centriole transforms into a basal body that templates the ciliary axoneme. Ciliogenesis depends on mother centriole-specific distal appendages, whereas the role of subdistal appendages in ciliary function is unclear. Here, we identify CEP128 as a centriole subdistal appendage protein required for regulating ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 34 publications
5
54
1
Order By: Relevance
“…In this study, we first carried out a database analysis to identify candidates for centriolar appendage components and independently found that Cep128 is localized to the SDA, in accordance with another report (Mazo et al, ; Mönnich et al, ). We then analyzed the topological relationship of fluorescently labeled protein components of SDAs by super‐resolution structured illumination microscopy (SR‐SIM).…”
Section: Introductionsupporting
confidence: 87%
“…In this study, we first carried out a database analysis to identify candidates for centriolar appendage components and independently found that Cep128 is localized to the SDA, in accordance with another report (Mazo et al, ; Mönnich et al, ). We then analyzed the topological relationship of fluorescently labeled protein components of SDAs by super‐resolution structured illumination microscopy (SR‐SIM).…”
Section: Introductionsupporting
confidence: 87%
“…[17] Mass spectrometry successfully revealed novel functions of proteins of primary cilia in regulating TGFβ/bone morphogenic protein signaling [23] and FGF signaling. For example, transcriptome analysis uncovered that TGFβ signaling that is activated at the ciliary pocket, the proximal part of the primary cilium residing in the cytoplasm within an invagination of the plasma membrane, is associated with differentiation into cardiomyocytes.…”
Section: Future Directionsmentioning
confidence: 99%
“…Indeed, recent work showed that CEP128 localizes to the SDA of the basal body to control ciliary recruitment of RAB11, and CEP128 loss leads to impaired TGF‐β/BMP signalling at the cilium in mammalian cells and in zebrafish embryos. Consequently, Cep128 morphants displayed defective organ development and other phenotypes indicative of compromised TGF‐β/BMP signalling . Furthermore, TGF‐βRI/II were shown to be targeted to the primary cilium by ARL6 to stimulate SMO in Hedgehog signalling, which is overactivated in metastatic cancer cells due to defects in ceramide‐mediated interaction between TGF‐βRI and SMAD7 that under normal conditions limits ciliary receptor localization .…”
Section: Overview Of Signalling Pathways Coordinated By Primary Ciliamentioning
confidence: 99%
“…). Accumulating evidence has implicated primary cilia, which are nonmotile versions of the organelle found in a single copy on most cell types in our body, in regulation of multiple cellular signalling pathways during development and in the adult, including Hedgehog and G‐protein‐coupled receptor (GPCR) signalling , as well as WNT and planar cell polarity (PCP) , receptor tyrosine kinase (RTK) , Notch , TGF‐β/BMP , Hippo , mTOR and polycystin signalling . The ability of primary cilia to regulate signalling relies on carefully orchestrated trafficking of membrane receptors and other signal transducers into and out of the organelle, both constitutively and in response to specific cellular and environmental stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation